MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DI SD NEGERI 012 SEI LALA KECAMATAN SUNGAI LALA KABUPATEN INDRAGIRI HULU - Partini Partini (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
The learning activities of Social Sciences (IPS) are part of the process of education in schools and have a role in life. One of them is thatsocial studies education has an important role in educating the life of the nation. Therefore, from time to time efforts are always made toimprove the quality of social studies education. Recognizing the importance of social studies education, efforts need to be made to improvethe learning process to improve student learning outcomes. Class action research is an improvement in the learning process to solveproblems faced by teachers in the classroom. Data obtained after research on teacher activities in the first cycle of the 1st meeting with apercentage of 50%, the second meeting with a percentage of 63%, in the second cycle at the third meeting percentage of 77%, and at the 4thmeeting the percentage obtained 86%. Observation data of student activities in this study obtained the percentage of the first cycle of the firstmeeting amounted to 52%, the second meeting was 61%, in the second cycle the third meeting was 75%, and the fourth meeting wasobtained 85% percentage proved that student activity has increased. Data on increasing learning outcomes of students in grade V SDN 012Sei Lala Kecamatan Sungai Lala in the initial data obtained an average of 60, in the daily test I obtained a class average of 75, and in dailytests, II obtained an average of 86. This proved that the STAD cooperative model in social studies learning is effectively used to improvesocial science learning outcomes of fifth-grade students.